AVALIAÇÃO DA PERDA HÍDRICA E DO GRAU DE CONHECIMENTO EM HIDRATAÇÃO DE ATLETAS DE FUTEBOL AMERICANO - Sara Ilda Fantinel Pinto; Valéria Stupka Berdacki; Simone Biesek (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Introduction: The American Football is on the rise in Brazil, and therefore, there are not many studies regarding hydration of the athletes in the sport. Players generally perform aerobic activities but there are moments of anaerobic activities. The uniform of this modality can aggravate the thermal stress of the player and is characterized as an activity that requires a systematic control of hydration. Objective: evaluate the water loss and the degree of knowledge on hydration of american football players. Materials and Methods: investigated 23 male athletes, between 18 and 38 years, of an amateur club in Curitiba. A survey was applied from an adaptation of Brito et al., (2006), containing 13 objective questions and estimated the percentage of weight loss and urinary density in a training day. Were performed the U of Mann-Whitney (p<0,05) and multiple linear regression Forward (p<0,10) tests. Results: through linear regression test, was discovered a direct association between the degree of knowledge and weight loss. The average weight loss was less than 2%. Conclusion: we observed a low level of knowledge on the part of the athletes on hydration being directly associated with weight loss.